Antibacterial activity of flavonoid isolated from jamblang leaves (Syzigium Cumini (L.) Skeels) against Staphylococcus aureus - Sania Nabila; Wulandari Wulandari; Endang Dwi Wulansari (Journal of Health Management and Pharmacy Exploration, 2023)
Jamblang leaves (Syzigium cumini (L.) Skeels) is one type plants used as traditional medicine. Jamblang leaves contain several phytochemical compounds such as alkaloids, flavonoids, resins, tannins, and oils essential. Flavonoid compounds contained in jamblang leaves have as antibacterial ability. The identification of flavonoid compounds in jamblang leaves and the antibacterial activity of flavonoid compounds against Staphylococcus aureus have been carried out. This study was conducted from jamblang leaves (Syzigium cumini (L.) Skeels) at concentrations of 2%, 4% and 6% against the growth of Staphylococcus aureus bacteria and to determine the type and structure of flavonoid compounds that have antibacterial activity. The method used for the extraction is remaceration, the separation of compounds using preparative thin layer chromatography while the antibacterial activity test using the pitting method and identification of flavonoid compounds using UV-Vis spectrophotometry. Extraction of 500 g of jamblang leaf powder using 96% ethanol resulted in a yield of 22,08%. The results of the study tested the antibacterial activity of flavonoid compounds of jamblang leaves obtained an average of clear zones produced at concentrations of 2%, 4% and 6% consecutively amounting to 0.9540 cm; 1.0540 cm; 1.1583 cm and ciprofloxacin 0.005 % by 1.4077%. Based on statistical analysis of the SPSS program with anava test 1 way obtained the results of significant activity differences between concentrations. Identification of the structure in UV-Vis spectrophotometry shows that flavonoid compounds lead to 3,7,4' trihydroxy flavonol.